Exon-capture data resolve relationships resulting from a rapid radiation within family Gobiidae - Johnson, Kendall; Tornabene, Luke; Li, Chenhong; Rüber, Lukas; Schliewen, Ulrich; Hogan, Derek; Pezold, Frank (Molecular phylogenetics and evolution, 2025)
[Display omitted] •All 14 previously-identified lineages in Gobiidae were recovered as monophyletic.•For the first time, relationships among the major gobiid lineages were confidently resolved.•There remains some ambiguity as to the sister clade of the Gobiosomatini-lineage.•Exon-capture can resolve phylogenetic relationships of rapidly-evolved clades. The family Gobiidae is the most speciose family within the Gobioidei, and is also historically the most poorly resolved due to a short period of rapid diversification early in the evolutionary history of the group. Their taxonomic and ecological diversity makes them ideal subjects for the study of many topics of ecology and evolution, including the evolution of behavior and life history traits, ecological and morphological adaptation, and speciation. However, the ability to understand and study these topics in gobies will remain limited until the phylogenetic relationships within the family have been resolved. Previous studies have identified 14 lineages within the family, but the relationships among those lineages are ambiguous, and more data is necessary to confidently determine those relationships. This study used exon-capture to obtain sequence data for hundreds of protein-coding loci to create a high-resolution phylogeny of Gobiidae to confidently resolve the interrelationships of the major lineages within the family. The monophyly of all previously identified groups was well-supported, as were the interrelationships among all but three of the 14 lineages, and results were consistent among different subsets of our data as well as different phylogenetic inferences. The major area of uncertainty included two competing hypotheses regarding the placement of the Gobiosomatini-lineage, and alternative hypotheses for this group are discussed in light of previous phylogenetic studies. Overall, the results represent a promising example of how gene-capture can resolve the taxonomy of problematic relationships that result from periods of rapid radiation.